Miniatures in Islamic Astrologic Manuscript of Oriental Institute in Sarajevo - Janc, Zagorka (Prilozi za orijentalnu filologiju, 2017)
At the Oriental Institute of Sarajevo, in the collection No 150/52, may be seen part of an astrological record dating from the 15th century. The manuscript has 22 sheets (format 26x17 cm). The text is written in Arabic, and partly in Turkish. The sheets 14 to 20 of the text contain miniatures with illustrations of the signs of the zodiac and a topical accompanying commentary. The manuscript is one of a series that originated in the times of Mongol rule in those parts. Besides this main influence the manuscript shows the influence of Mongolian costume and weapons, as well as traces of some elements taken from the Indian Buddhist art.